The Effect of Profitability and Company Size on Firm Value with Capital Structure as a Moderating Variable (Empirical Study of the Industrial Sector Listed on the IDX for the 2019-2021 Period) - Via Nurul Izzah; Ira Hapsari; Novi Dirgantari; Annisa Ilma Hartikasari (Formosa Journal of Applied Sciences, 2023)
The value of industrial sector companies continued to decline in the 2019-2021 period, which indicates that company performance in the industrial sector is still not good. Companies need to pay attention to what factors have an impact on the value of the company so that they can always increase the performance and value of the company. This study aims to empirically examine the influence of Profitability and Firm Size on Firm Value with Capital Structure as moderator. The population of this study is 56 industrial sector companies listed on the IDX for the 2019-2021 period with 44 sample data. Sampling was taken using purposive sampling method, and data analysis was using Moderated Regression Analysis (MRA) using the SPSS program. The results of this study prove that profitability has a positive impact on firm value, firm size does not affect firm value, capital structure cannot moderate the impact of profitability on firm value, capital structure can strengthen the impact of firm size on firm value. The results of this study contribute to industrial sector companies in an effort to increase the value of their companies.